PERAN RELASI ANTARA PERUSAHAAN DAN PEMASOK DALAM PROSES PEMBELIAN BAHAN BAKU DI BISNIS KECIL - Maria Pampa Kumalaningrum (Fakultas Bisnis UKDW, 2012)
This study aimed to examine the role of buyer-supplier relationship in the relationship betweenbuyer specificity and organizational performance. Data was processed with StructuralEquation Modeling using AMOS program. The result showed that buyer specificity hasdirect effect on buyer-supplier relationship, and buyer-supplier relationship has direct effect onorganizational performance. The results of this study provide insight into the development andimpact of buyer-supplier relationship within small business organizations.Keywords: buyer-supplier relationship, buyer specificity, organizational performance